2015
DOI: 10.1590/bjpt-rbf.2014.0076
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of different methodologies of infrared image analysis of myofascial trigger points in the upper trapezius muscle

Abstract: BACKGROUND:Infrared thermography is recognized as a viable method for evaluation of subjects with myofascial pain. OBJECTIVE: The aim of the present study was to assess the intra- and inter-rater reliability of infrared image analysis of myofascial trigger points in the upper trapezius muscle. METHOD: A reliability study was conducted with 24 volunteers of both genders (23 females) between 18 and 30 years of age (22.12±2.54), all having cervical pain and presence of active myofascial trigger point in the upper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
29
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 38 publications
1
29
0
3
Order By: Relevance
“…Compared to other imaging modalities, the thermal image interpretation is easier and faster method which is apparent from the images acquired during the study, similar to findings by Merla et al wherein they distinguished between healthy patients and patients suffering from myofascial pain using functional infrared imaging [13][14][15]. Gratt and his colleagues classified the patients with chronic orofacial pain as normal, hot or cold when the temperature in a selected anatomic area (∆T) fell between certain assigned ranges [16], [17]. The current study reinforces the findings of the study made by Gratt et al, since temperature was found to be significantly elevated in subjects with dental issues in comparison with normal subjects.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Compared to other imaging modalities, the thermal image interpretation is easier and faster method which is apparent from the images acquired during the study, similar to findings by Merla et al wherein they distinguished between healthy patients and patients suffering from myofascial pain using functional infrared imaging [13][14][15]. Gratt and his colleagues classified the patients with chronic orofacial pain as normal, hot or cold when the temperature in a selected anatomic area (∆T) fell between certain assigned ranges [16], [17]. The current study reinforces the findings of the study made by Gratt et al, since temperature was found to be significantly elevated in subjects with dental issues in comparison with normal subjects.…”
Section: Discussionsupporting
confidence: 62%
“…They obtained excellent inter-rater reliability for point and line analysis with inter class correlation co-efficent equal to 0.908 and 0.918 respectively. They finally suggested that the infrared imaging technology was suitable for diagnosis of myofascial trigger points in the upper trapezius muscle in clinical and research practices [18]. Rodriguesbigaton et al (2013) predicted the temporomandibular (TMD) disorder in arthralgia patients using thermal imaging technique with good accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…The authors analysed the images using two techniques, muscle length (using a line ROI) and muscle central portion (point measurement) and based in the 95% CI the ICC values ranged between 0.992 and 0.999 when using the line ROI and between 0.778 and 0.999 using the point measurement. Another study [33] assessed the interrater and intrarater reliability of three methodologies of analysing skin temperature over the upper trapezius muscle (point, line and area) and found that the reliability when using the mean was higher than when using minimum or maximum values. The ICC values for mean temperature were similar for the three methodologies, with ICC values ranging between 0.915 and 0.996.…”
Section: Discussionmentioning
confidence: 99%
“…The ICC values were slightly better when using the point methodology. It is important to note that both Costa, Dibai Filho, Packer and Rodrigues-Bigaton [32] and Dibai-Filho, Guirro, Ferreira, Brandino, Vaz and Guirro [33] used styrofoam markers to delineate the ROIs, which may have contributed to increase the reliability of the analysis. One study [29] assessed the interrater and intrarater reliability of analysing thermal images of the breasts and reported ICC values ranging between 0.948 and 0.999.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation